The Effectiveness of Imagery Exercise on Improving the Technical Skill of a Basketball Lay-Up - Dimyati (ANIMA Indonesian Psychological Journal, 2014)
The purpose of this study is to determine the effectiveness of imagery training on improving the technical skill of a basketball lay-up for students of Faculty of Sports Education, Yogyakarta State University (FIK UNY). The method used in this research was an experimental design with pre-test post-test control group. The population of this study was the new students of FIK UNY academic year 2013/2014. Samples were taken using the proportional random sampling technique. To prove the research hypothesis, a t-test statistical technique was used. Based on the analysis of data, tcount was 2.177 with p < .05. This means that there is a significant difference in the lay-up technical skill between the control group and the experimental group. The experimental group had a higher mean score of improvement in lay-up technical skill compared to the control group. Thus it can be concluded that imagery exercise improves the basketball lay-up technical skill for students of FIK UNY. The result in basketball lay-up of students who were given the exercise program and the imagery exercise is significantly higher than the students who were given a lay-up shot exercise program without imagery exercise. Penelitian ini bertujuan untuk mengetahui efektivitas latihan imajeri terhadap peningkatan keterampilan teknik lay-up shoot Bolabasket mahasiswa FIK UNY. Metode yang digunakan dalam penelitian ini adalah desain eksperimen dengan teknik pretest-posttest control group design. Poluasi dalam penelitian ini adalah mahasiswa baru FIK UNY tahun akademik 2013/2014. Teknik pengambilan sampel menggunakan proportional random sampling. Teknik analisis data untuk membuktikan hipotesis penelitian menggunakan statistik uji t. Berdasarkan hasil analisis data diperoleh thitung 2,177 dengan p < .05. Ini berarti terdapat perbedaan yang signifikan keterampilan teknik lay-up shoot antara kelompok kontrol dengan kelompok eksperimen. Kelompok eksperimen memiliki rerata peningkatan keterampilan teknik lay-up shoot yang lebih tinggi dibandingkan kelompok kontrol. Penelitian ini menyimpulkan bahwa latihan imajeri memiliki efektivitas terhadap peningkatan keterampilan teknik lay-up shoot Bolabasket mahasiswa FIK UNY. Peningkatan teknik lay-up shoot Bolabasket pada mahasiswa yang diberi program latihan lay-up shoot ditambah latihan imajeri lebih tinggi dibandingkan dengan mahasiswa yang diberi program latihan lay-up shoot tanpa ditambah latihan imajeri.